Soft tissue neoplasms: a clinicopathological study - K. T., Athulya Krishna Kumar; S., Ariya (International Journal of Research in Medical Sciences, 2020)
Background: The current WHO classification has categorized soft tissue tumours into benign, malignant and so-called intermediate neoplasms. Soft tissue sarcoma comprises <1% of adult cancers. The aim of the study was to clinically correlate soft tissue neoplasms and study the histomorphological features of various malignant soft tissue tumors. Methods: This was a retrospective study conducted in a tertiary care hospital in Mangalore, India from January 2019 to June 2020. Clinical details of all cases of soft tissue neoplasms retrieved from the medical records of our institution. Data collected included age, gender, presenting symptoms, site and size of soft tissue neoplasms and clinical diagnosis. Pathological diagnosis of these tumours was made and details recorded. Results: A total of 113 cases of soft tissue neoplasms were collected. 94.4% benign and 18.6 %. malignant tumours were present. 77% cases presented with swelling whereas 23% presented with pain. Majority of benign soft tissue tumours were located in the trunk (36.9%) and the most common type was lipomas (66.38%). Malignant soft tissue tumours showed male to female ratio of 1.33:1. Most predilection was noted for the extremities (42.8%) and leiomyosarcomas were the most common type (38%). Conclusions: The incidence of malignant soft tissue tumours is rare. Majority of the cases were noted in the extremities. Leiomyosarcoma was the most common type, in our study. Lipomas were the most common benign soft tissue tumours, and majority of the benign tumours were located in the trunk.